Association between Physical Fitness and Perceived Well-Being in Functionally Independent Community Dwelling Elderly of North-Eastern India - Bhattacharya, Prasanta Kumar; Deka, Kuldeep; Barman, Bhupen; Jamil, Md (Acta medica Lituanica, 2023)
Background: Regular physical activity helps in independent living, prevention of chronic health problems and quality of life in the elderly. The aim of the study is to determinewhether physical fitness is associated with multiple dimensions of well-being in the community dwelling elderly. Materials and Methods: A community-based cross-sectional study was undertaken to assess the physical fitness and perceived wellness in 400 elderly (≥65 years) subjects. The Senior Fitness Test (SFT) for assessing functional/physical fitness and Perceived Wellness Survey (PWS) were used to assess their well-being. Bivariate correlation analysis was used for individual testsand multiple linear regressions were used to analyze relationship of wellness composite score with physical fitness test.XXXX Results: 284men and 116 women (mean ages 69.80±3.82 and67.25±2.57 years, respectively) were assessed for physical fitness tests and perceived wellness.‘Arm-curl’ and ‘chair-sit’ testsshowedlinear decrease in strength with increasing age. In ‘back-scratch’ and ‘chair-sit and reach’ tests lower limb flexibility was better than upper limb in all except the 65–69 year sub-group. Maximum time to perform the ‘8-feet up-and-go’ test increased progressively with age, whereas ‘2-minute step’ test showed a linear decrease in mean score with advancing age. Wellness composite score (14.54±2.31) inmaleswas maximum in the 75–79 year age-group, while in females it (15.26±2.29) was maximum in the 70–74 year age-group. Correlation analysis of physical fitness test with perception of wellness (composite score) showed significant association of ‘arm-curl’ test (p=0.012), ‘back-scratch’ test (p=0.0002), ‘8-feet up-and-go’ test (p=0.005), ‘2-minute step’ test (p=0.005) with the composite wellness score in the male participants, whereas in the females such significance was observed only in the ‘2 minute step’ test (p=0.007) with the wellness score. Conclusion: Screening of physical fitness and wellness are important measures in assessing wellness of community dwelling elderly, and in predicting theiroverall state of well-being, including age-specific comparison of fitness performance and wellness score.